Electrical power distribution : case studies from Distribution Reform, Upgrades and Management (DRUM) Program (McGraw-Hill's AccessEngineering., 2012)
"The power distribution sector in India ails from high AT&C losses, deteriorating infrastructure, low access, and poor financial health of most utilities. The issues get compounded due to low focus on service quality and consumer welfare. We are not yet ready to treat electricity 'consumers' as 'customers' while some sectors like airlines have started treating 'passengers' as 'guests'. The pressure of low carbon economy has further exacerbated the problem. Through the case studies in this book, we are trying to show a small way to overcome some of these hurdles. We present here some live examples of technology and process interventions which have the potential to significantly improve the distribution sector. The section on Smart Grid suggest the direction in which Indian distribution utilities should focus to take leap frog advantage of this game changing vision for a better future. DRUM Project has been a "DREAM COME TRUE". Case studies presented in this book are Live Experiences of these Success stories, which Indian Utilities can just adopt. These case studies show that with various technical and process interventions KPIs of utilities can be drastically improved. The book will be very useful to Power Distribution System Planners, particularly on backdrop of R-APDRP schemes for Urban/ Semi Urban areas, Distribution Operation Engineers and academicians. The Book is really the "Need of Hour" " -- .V. L. Sonavane, Member (Technical), Maharashtra Electricity Regulatory Commission, Mumbai. "An impressive collection of content for electricity distribution practices. The book incorporates the lessons learnt during implementation and modernization of infrastructure for electricity distribution systems. Technologies described in the case-studies can be easily extended to futuristic electricity distribution systems, such as smart grids." -- Prof. Prem K. Kalra, Director, IIT Rajasthan. "The DRUM initiative of US Rural Utility Services and USAID created a paradigm shift in power utility planning from consumers' perspective. The case studies on Indian utilities in the book give valuable insights for a need to shift focus on bottom up approach for balanced power sector development." -- Ramesh Narayanan, CEO-BSES Yamuna Power Ltd. "DRUM has created many success stories and has established replicable models for implementation of technology and best practices for distribution of electricity in urban and rural areas of the country. DRUM team has developed many case studies of these experiences and has brought it out in the form of a book so that power sector can use the experiences of the program to its advantage. These case studies are designed in a way that it benefits utilities, academic institutions, institutions providing finance, and technology and practicing professionals." -- Prof. Atmanand Dean, School of Energy Management, Management Development Institute (MDI) Gurgaon, India.